Rationality and the illusion of choice - Evans, Jonathan S. (Frontiers in Psychology, 2014)
The psychology of reasoning and decision making (RDM) shares the methodology of cognitive psychology in that researchers assume that participants are doing their best to solve the problems according to the instruction. Unlike other cognitive researchers, however, they often view erroneous answers evidence of irrationality rather than limited efficiency in the cognitive systems studied. Philosophers and psychologists also talk of people being irrational in a special sense that does not apply to other animals, who are seen as having no choice in their own behaviour. I argue here that (a) RDM is no different from other fields of cognitive psychology and should be subject to the same kind of scientific inferences, and (b) the special human sense of irrationality derives from folk psychology and the illusory belief that there are conscious people in charge of their minds and decisions.